Hubungan Tingkat Kecukupan Kalsium dan Kebiasan Merokok dengan Kepadatan Tulang Pada Wanita di Desa Klumpit Kabupaten Kudus - Noor Mafazah; Ali Rosidi; Yunan Kholifatuddin (Universitas Muhammadiyah Semarang, 2016)
Bone density is key to determining the magnitude of the risk of osteoporosis. Osteoporosis is characterized by decrease in bone strength and increase in fragility caused by low bone density. To prevent the low bone density, we can optimize the bone mass at the top of our growth, thats happen before we 30 years old. Smoking habit, exspecially on women can speed up the decrease of bone density, called osteopenia. By the survey, the prevalenceof osteopenia on smoker women is 29,4 %. Osteopenia on the smoker women will increase the risk factor of osteoporosis. The smoker women have the 6 th biger risk factor than the man. Beside smoker, the risk factor thats can increase the osteoporosis incident on women are decreasing estrogen hormonon 30 years old, the lengt of breastfeeding, fisical activity, alcohol and cafein consumption, and dietary of calcium, fosfor, vitamine D, fluorida, kalium, and protein.The objective of this study was to determine the relationship of calcium adequacy levels, and smoking habit and bone density of women at Klumpit village,Kudus District. Observasional study with a survey method and cross-sectional approach was conducted in the village of Klumpit, Kudus district. The number of sampel is 60 women who 26-44 years old, consist of 30 smoker women and 30 not smoker women. The sampling method is stratifiedrandom sampling. The data collecting by interview, FFQ and Quantitative Ultrasound Bone Densitometry. The test of normally distributed of the variable data was conducted by Shapiro Wilk test. The variable correlation test was conducted by applying Pearson Product MomentorRank Spearman.The result show that the respondens average of calcium intake is 97,58 mg/days 12,89 mg/days. There are 43,3 % of the women are calcium deficiency. The smoker women smoke by the average of 4,67 0,5 cigarete/day. The average of bone density is 1,29 gram/cm 0,212 gram/cm 2.The lowest bone density is 1.8 g/cm2 and the highest is 4.5 g/cm2. There are 23,3 % of responden who suffer the osteopenia and 40 % of the other were osteoporosis.The rankspearman test show there was a strong significant positive correlation between calcium adequacy level and bone density (r = 0,619 and p = 0,000)and there was a significant negative correlation between smoking habit and bone density (r = -0,488 and p = 0,000).Increasingly the smoke freqeuncy wil more decrease the bone density. The bone density strongly related to the level of calcium adequacy and smoking habits on womens at Klumpit village, District of Kudus.Keywords:Calcium adequacy level, smoking habit, bone density